Morphological and physiological response of Chinese tallow (Triadica sebifera) to an extreme cold spell in subtropical, coastal forests of China - Xie, Hongtao; Pile Knapp, Lauren S.; Yu, Mukui; Wang, G. Geoff (Frontiers in Ecology and Evolution, 2022)
Acute and extreme weather events can cause considerable damage to the tissues of trees, including stem death and branch or leaf distortion, which may limit their survival and reproduction. In January 2016, a rare cold spell impacted the coastal forests of subtropical China. Using post-hoc assessments, we evaluated the morphological and physiological response of Chinese tallow (Triadica sebifera L.) to the extreme cold spell in two distinct ecoregions, one (Xiangshan, China) representing the cold spell impacted zone and the other (Taizhou, China) representing the non-affected zone. To determine if the extreme cold events impacted the vigor of Chinese tallow, we assessed differences in growth rate, leaf characteristics, and leaf gas exchange. As age may affect tree morphological and physiological response to stress, we grouped subject trees into three distinct cohorts, namely, seedlings (1-2 years old), young-aged (5-6 years old) and middle-aged (10-12 years old). Our results suggest that although tree height and diameter did not differ, leaf area expansion and leaf mass were reduced in the impacted zone. In seedling and young-aged trees, the cold spell significantly reduced leaf net photosynthetic , transpiration rates , stomatal conductance and water use efficiency while leaf intercellular CO2 concentration, vapor pressure deficit , and intercellular CO2 pressure increased. In contrast, the middle-aged group was less responsive to the cold spell. Across all cohorts, the activity of superoxide dismutase and peroxidase decreased. We also detected increases of leaf malondialdehyde and free proline contents in young-aged and middle-aged groups. Hence, the extreme cold spell caused remarkable negative effects on the morphological and physiological traits of Chinese tallow. Redundancy analysis revealed that the cold spell also impacted the subsequent recovery process of damaged Chinese tallow by reducing the ability of leaf to utilize microenvironmental resources (radiation, air humidity and CO2) for gas exchange. Results from this study are important to strengthen our understanding of Chinese tallow responding to extreme cold stress within its native range, also be helpful to predict the distributions of Chinese tallow in its invasive range where it has devastating impacts to coastal ecosystems in the southeast US.